A Polarization Migration Velocity Model Building Method for Geological Prediction Ahead of the Tunnel Face - Wang, Bo; Huang, Lanying (Frontiers in Earth Science, 2022)
It has been difficult to establish velocity models that use reflected seismic signals with advanced prediction ahead of the tunnel face. The accurate establishment of advanced velocity models face issues including artifacts in migration results and incorrect calculation of velocity. This study presents a polarization migration velocity model building method to solve these issues. First, the artifacts in migration interfaces were eliminated by the polarization characteristics of three-component reflected signals. Second, the optimum velocity ahead of the tunnel face was determined according to the energy stack characteristics of common interface points. Finally, the velocity model was established based on optimum velocity parameters and corresponding polarization migration interfaces using a three-dimensional and three-component numerical simulation conducted on faults with high dip and different inclinations. The results indicate that the velocity errors in the advanced velocity model were 1% and 2% for each of the two layers, and the position errors of the two interfaces were smaller than 3% and 2%. The experimental results of the Maanshan tunnel verified the effectiveness of the polarization migration velocity model building method.